METHODOLOGY FOR DEVELOPING STUDENTS' PHYSICAL AND TECHNICAL ABILITIES IN PHYSICS EDUCATION (World Bulletin of Education and Learning, 2025)
This paper presents a methodology for developing students’ physical-technical abilities in secondary school physics education. Emphasis is placed on practice-oriented laboratory work, including frontal (whole-class) experiments and creative technical tasks, as key strategies. The approach is designed not only to reinforce theoretical knowledge but also to enhance practical skills, technical thinking, and collaborative problem-solving among students. An overview of relevant literature and modern pedagogical technologies is provided, highlighting the importance of interactive and hands-on methods in physics teaching. The methodology and experimental results demonstrate significant improvements in students’ practical competencies, analytical thinking, and teamwork skills when active learning techniques are employed. In particular, students who participated in regular laboratory experiments and technical problem-solving activities showed higher levels of engagement and roughly 10% greater learning gains compared to those taught by traditional methods. The discussion addresses how these findings align with educational reforms and modern STEM approaches. It concludes with recommendations to integrate practice-oriented methods more widely to foster students’ scientific interest, creativity, and readiness for future technological endeavors.
Keywords: Physics education; technical abilities; laboratory experiments; practical skills; STEM approach.